Bridging inflammation and venous thrombosis: the NLRP3 inflammasome connection - Wu, Jian; Wang, Zilong; Shao, Wei; Mo, Jianwen (Frontiers in Cardiovascular Medicine, 2025)
NLRP3 (NACHT, LRR, and PYD domains-containing protein 3) inflammasome is a critical regulator of inflammatory responses in the body and is closely associated with the inflammatory processes of various diseases. In recent years, research has increasingly focused on the role of the NLRP3 inflammasome in venous thromboembolism (VTE). Venous thromboembolism is a common and potentially fatal vascular disease with a complex pathophysiology involving multiple cellular and molecular pathways. The NLRP3 inflammasome activates caspase-1 downstream, facilitating the maturation and secretion of pro-inflammatory cytokines such as IL-1β and IL-18, triggering local and systemic inflammatory responses. These inflammatory reactions can promote the recruitment and activation of immune cells (such as monocytes and neutrophils), platelet activation, endothelial cell damage, and aggregation, ultimately leading to thrombus formation. Additionally, the interaction of the NLRP3 inflammasome with the coagulation system further exacerbates the risk of thrombosis. In summary, the NLRP3 inflammasome plays a critical role in the development of venous thrombosis, and interventions targeting it may offer new insights and strategies for the prevention and treatment of venous thrombosis. This review provides an overview of the current understanding of how the NLRP3 inflammasome promotes venous thrombosis, highlighting recent preclinical research advancements and potential therapeutic agents in this field.